Sequencing therapy in advanced prostate cancer: focus on sipuleucel-T. Issue 1 (January 2014) - Quinn, David I; Vaishampayan, Ulka; Higano, Celestia S; Lin, Daniel W; Shore, Neal D; Beer, Tomasz M
Abstract : Immunotherapies such as sipuleucel-T present new and unique challenges for the optimal timing and sequencing of therapies for metastatic castration-resistant prostate cancer (mCRPC). Key considerations for the sequencing of sipuleucel-T are its unique proposed mechanism of action, the time required to generate a clinically relevant immune response, and the observed efficacy in Phase III trials in 'early' or asymptomatic or minimally symptomatic mCRPC. There are three broad timing and sequencing options for sipuleucel-T in patients with rising prostate-specific antigen and radiologic evidence of disease: immediately after androgen-deprivation therapy failure, after failure of secondary hormonal maneuvers, or after chemotherapy. There are several other agents in Phase III development in mCRPC and any future approvals will impact on the current treatment algorithm, and raise further questions regarding how to optimize sequencing and timing of therapies for better clinical outcomes.